2020
DOI: 10.1039/d0gc00775g
|View full text |Cite
|
Sign up to set email alerts
|

Reporting the unreported: the reliability and comparability of the literature on organic solvent nanofiltration

Abstract: The way forward to improve and standardize membrane reports, and to bridge the gap between academic efforts and industrial requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…The TFC membranes are usually prepared using different methods, solvent systems, diverse monomers, and some additives like a nanomaterial including zeolites, silicalites, quantum dots (QD), and graphene oxides (GO). Performance test is conducted under a cross-flow or dead-end configuration system with diverse parameters such as pressure, temperature, agitation rate, and different concentration of solutes in various solvents [ 88 ]. Performance in the RO system is easy to compare each other since the fixed concentration of sodium chloride in water and operation conditions have been used [ 88 ].…”
Section: Materials For Tfc Membranementioning
confidence: 99%
See 1 more Smart Citation
“…The TFC membranes are usually prepared using different methods, solvent systems, diverse monomers, and some additives like a nanomaterial including zeolites, silicalites, quantum dots (QD), and graphene oxides (GO). Performance test is conducted under a cross-flow or dead-end configuration system with diverse parameters such as pressure, temperature, agitation rate, and different concentration of solutes in various solvents [ 88 ]. Performance in the RO system is easy to compare each other since the fixed concentration of sodium chloride in water and operation conditions have been used [ 88 ].…”
Section: Materials For Tfc Membranementioning
confidence: 99%
“…Performance test is conducted under a cross-flow or dead-end configuration system with diverse parameters such as pressure, temperature, agitation rate, and different concentration of solutes in various solvents [ 88 ]. Performance in the RO system is easy to compare each other since the fixed concentration of sodium chloride in water and operation conditions have been used [ 88 ]. However, it is very difficult to fairly compare membrane performance owing to more complex testing system with diverse solvent–solute combinations and operating conditions.…”
Section: Materials For Tfc Membranementioning
confidence: 99%
“…The use of dead-end configuration was due to its low volume requirement, cost-effectiveness and ease of operation. By using a dead-end configuration, researchers would have an ample resource allocation to obtain a rough performance estimate of a membrane separation, as a cross-flow filtration unit costs 10-20 times as compared to a dead-end filtration unit (Le Phuong et al, 2020). According to Shi et al (2019), it was found that the permeance values in cross-flow filtration was higher than that of dead-end filtration.…”
Section: Membrane Systemmentioning
confidence: 99%
“…Organic solvent nanofiltration (OSN), also called solvent-resistant nanofiltration (SRNF), is a pressure-driven sustainable separation technology applied in fine chemical and petrochemical purification, which can separate solutes between 50 and 2000 g mol −1 in a wide range of organic solvents [31]. OSN is a predictable and energy-efficient technology compared to other separation techniques such as distillation, chromatography, and extraction [32].…”
Section: Introductionmentioning
confidence: 99%